Prevalence Rate of Rheumatoid Arthritis among Patients Attending Rheumatology Consultation Clinic at Baquba Teaching Hospital - Muayad Kadhim Rashid (Diyala Journal of Medicine, 2023)
Background: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease that causes progressive and painful of multiple joints damage. Objective: To explore the prevalence of Rheumatoid arthritis (RA) among middle-aged and older of Iraqi patients attended the outpatients’ clinics.